An in vitro study of bacterial survival in response to high-intensity nanosecond pulse stimulation - Soraya Chaturongakul (2018)
Effects of 3-kJ.kg -1 nanosecond pulsed electric fields on activities of Salmonella enterica and Staphylococcus aureus were observed through batch treatment experiments. The results showed different responses in bacterial inactivation depending on pulse durations (30 and 500 ns) and bacterial strains. The response to longer pulse treatments of S. enterica showed a higher significance in bacterial inhibition effect while S. aureus appeared to have higher resistance to both pulse durations. Among treatments, a maximum average reduction of 2.5 log10 cycles occurred when stimulating S. enterica with 25 kV.cm -1 , 500 ns pulses for a total treatment time of 300 s. Such inactivation mechanisms could be explained through the behavior of an equivalent circuit associated with the properties of cell wall composition. © 2012 IEEE.